The Palgrave Handbook of Magical Realism in the Twenty-First Century
XXI, 650 p. 2 illus., 1 illus. in color.
Keywords: The Palgrave Handbook of Magical Realism in the Twenty-First Century examines magical realism in literatures from around the globe. Featuring twenty-seven essays written by leading scholars, this anthology argues that literary expressions of magical realism proliferate globally in the twenty-first century due to travel and migrations, the shrinking of time and space, and the growing encroachment of human life on nature. In this global context, magical realism addresses twenty-first century politics, aesthetics, identity, and social/national formations where contact between and within cultures has exponentially increased, altering how communities and nations imagine themselves. This text assembles a group of critics throughout the world—the Americas, Europe, Africa, Asia, the Middle East, and Australia—who employ multiple theoretical approaches to examine the different ways magical realism in literature has transitioned to a global practice; thus, signaling a new stage in the history and development of the genre. .